Aqueous extraction, purification and characterization of galactomannans from aren sugar palm (Arenga pinnata) fruits - Meor Hussin, Anis Shobirin; Che Wan Sapawi, Che Wan Nur Safraa; Anzian, Aliaa; Ramli, Hajar Balkhis (Indonesian Society for Knowledge and Human Development, 2017)
The effect of different aqueous extraction conditions on the crude gum extraction yield of Aren sugar palm (Arenga pinnata) fruit was evaluated. A water-soluble polysaccharide was extracted from the endosperm of A. pinnata fruit with water at different extraction conditions. The results indicated that water to seed ratio, alkaline pH and temperature were significantly (p<0.05) effect the extraction yield of the crude gum. The ideal extraction conditions (W/S ratio: 20:1, pH: 10 and temperature: 80˚C) led to the highest yield (5.50%) of the A. pinnata fruit gum. The purified gum was characterized as white, thread-like precipitate and become a powder-like substance after being freeze dried. It had relatively low protein content (1.15%) and partially solubilised at ambient (50.93%) and at elevated temperature (71.00%). The gum had a high water holding capacity but lower oil-holding capacity which was 150.00 g water/100 g and 103.33 g oil/100 g of gum respectively. The viscosity of the purified gums increased with the increase of solution concentration. This revealed that A. pinnata gum is suitable for applications as stabilizer for oil-in-water emulsion or as food additives due to its capability to hold water molecules and form a viscous solution at low concentration.